2017
DOI: 10.1155/2017/3524307
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen Inhibited Apoptosis of Osteoporotic Osteoblasts by Modulating IRE1-ASK1-JNK Pathway

Abstract: Osteoporosis is a common disease causing fracture in older populations. Abnormal apoptosis of osteoblasts contributes to the genesis of osteoporosis. Inhibiting apoptosis of osteoblasts provides a promising strategy to prevent osteoporosis. The proliferation of osteoblasts isolated from osteoporotic patients or healthy subjects was determined by MTT assay. Apoptosis was determined by Annexin V/PI assay. Protein expression was measured by western blot. The proliferation of osteoblasts isolated from osteoporotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated the effect of psoralen on osteoblast proliferation in vitro (29,30). To elucidate the mechanism of action of psoralen on osteoblast proliferation, the effects of psoralen on three primary signaling pathways, namely extracellular signal-related kinase (ERK), c-Jun N-terminal kinase (JNK) and MAPK, were determined by evaluating signal pathway activity and cell proliferation (Fig.…”
Section: Hfob119 Cell Proliferation Depends On Nk-κb-mapk Signalingmentioning
confidence: 99%
“…Previous studies have demonstrated the effect of psoralen on osteoblast proliferation in vitro (29,30). To elucidate the mechanism of action of psoralen on osteoblast proliferation, the effects of psoralen on three primary signaling pathways, namely extracellular signal-related kinase (ERK), c-Jun N-terminal kinase (JNK) and MAPK, were determined by evaluating signal pathway activity and cell proliferation (Fig.…”
Section: Hfob119 Cell Proliferation Depends On Nk-κb-mapk Signalingmentioning
confidence: 99%
“…Moreover, MG-63 osteogenic sarcoma cells were inhibited with 640 μmol/L psoralen treatment for 72 h, and the cell inhibition rate was 77.74%, and the cells became smaller, rounder, vacuoles and pseudopodia disappeared [34]. Although there are lots of studies about the pro-apoptotic function of psoralen, however, recent study demonstrated that psoralen could inhibit the apoptosis and increase the proliferation of osteoporotic osteoblasts by modulating IRE1-ASK1-JNK pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…NBIF in combination with psoralen or estradiol was observed to decrease the expression of Bax, p-JNK, IRE1, p-ASK and was also found to upregulate Bcl-2 expression. Thus synergistic regulation of IRE1-ASK1-JNK pathway by the combination of suppressed osteoporotic activity and osteoblastic apoptosis led to greater enhancement of bone mineralization ( Chen S. et al, 2017 ).…”
Section: Neobavaisoflavonementioning
confidence: 99%